Force–velocity relation for copolymerization processes. (23rd April 2015) - Gaspard, Pierre
Abstract: A study is reported of copolymerization processes subjected to an external force in the light of recent advances on the kinetics and thermodynamics of copolymer growth. Different processes are considered: the free copolymerization of Bernoulli and first-order Markov chains and copolymerization with a template. For every process, the dependence on the force is analyzed for the elongation rate, the growth velocity, the disorder in the copolymer sequence, the thermodynamic entropy production, as well as related quantities. It is shown that disorder in the copolymer sequence can generate forces of entropic origin. They are characterized by the value of their stall force in the force–velocity relation of the corresponding process.